1973
DOI: 10.1002/chin.197305141
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: CARBONYLIERUNGSRK. 3. MITT. UMSETZUNG VON KOHLENMONOXID MIT TRICYCLOHEXYLBORAN UNTER NORMALDRUCK

Abstract: Beim Einleiten von Kohlenmonoxid bei 100 ‐ 110°C in eine Lösung von Tricyclohexylboran (I) in Diglym in Gegenwart von Äthylenglykol (II) und metallischem Natrium tritt stürmische Wasserstoffabspaltung ein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[7] These reactions have attracted significant attention as they provide a direct route to various functionalized compounds, mainly including ketones and alcohols. [8] Alternative variants to carbonylation make use of cyanide (cyanidation) [9] or a carbenoid (carbenoidation) instead of CO. [10] The underlying mechanistic intricacies of these carbonylation reactions involve the activation of both CO and the CÀ B bond of the trialkyl borane, through the formation of the initial adduct that triggers the sequential B-to-C migratory insertion of one, [7c] two [7b] or all three B-substituents. [3,7a] To the best of our knowledge the first theoretical study on these sequential migratory insertion steps was long time back reported for Hshifts on H 3 BÀ C=X adducts (I) at the semiempirical MNDO or ab initio up to HF/6-31G*//HF/STO-3G levels, [11] as simplified models for carbonylation (X: O), cyanoborate protonation (X: NH) and alkinyl borate protonation (X: CH 2 ) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[7] These reactions have attracted significant attention as they provide a direct route to various functionalized compounds, mainly including ketones and alcohols. [8] Alternative variants to carbonylation make use of cyanide (cyanidation) [9] or a carbenoid (carbenoidation) instead of CO. [10] The underlying mechanistic intricacies of these carbonylation reactions involve the activation of both CO and the CÀ B bond of the trialkyl borane, through the formation of the initial adduct that triggers the sequential B-to-C migratory insertion of one, [7c] two [7b] or all three B-substituents. [3,7a] To the best of our knowledge the first theoretical study on these sequential migratory insertion steps was long time back reported for Hshifts on H 3 BÀ C=X adducts (I) at the semiempirical MNDO or ab initio up to HF/6-31G*//HF/STO-3G levels, [11] as simplified models for carbonylation (X: O), cyanoborate protonation (X: NH) and alkinyl borate protonation (X: CH 2 ) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%